Pengaruh Pelatihan Teknik Otomotif Terhadap Peluang Bekerja Di Industri Otomotif - Khoiri, Mukhtarul; Sudrartono, Tiris (Fakultas Ekonomi Universitas Gresik, 2023)
Job vacancies are the most sought after by the community. People find it difficult to get a job due to lack of skills, knowledge and motivation. As a result, various training venues and fields began to emerge and compete with each other to provide higher quality training. BBPLK Bandung is a current training venue, and always keeps abreast of developments. One of the training programs is in the field of automotive engineering. The purpose of this research is for the author to identify how the quality of training is, such as skills training, functional training, teamwork training, creativity training, and Productivity training can affect opportunities for employment in the automotive industry. The method used in this research is quantitative method and data collection uses a questionnaire with a total sample of 110 respondents. With the help of the IBM SPSS STATISTICS application, the data analysis method used in this study includes descriptive statistical analysis, inferential statistical analysis, which includes data normality test, Paerson product moment correlation coefficient test, coefficient of determination, simple linear test, f test, and t test Based on the research results, it can be concluded that H0 is rejected and H1 is accepted because the tcount value is 20,675 > ttable 0,186 with a significant level of 0.001 <0.05, meaning that the quality of automotive engineering training at BBPLK Bandung has a significant effect on job opportunities in the automotive industry